Early prediction of typical outcome and mild developmental delay for prioritisation of service delivery for very preterm and very low birthweight infants: a study protocol. Issue 7 (4th July 2016) - Caesar, Rebecca; Boyd, Roslyn N; Colditz, Paul; Cioni, Giovani; Ware, Robert S; Salthouse, Kaye; Doherty, Julie; Jackson, Maxine; Matthews, Leanne; Hurley, Tom; Morosini, Anthony; Thomas, Clare; et al.
Abstract : Introduction: Over 80% of very preterm (<32 weeks) and very low birthweight (<1500 g) infants will have either typical development (TD) or mild developmental delay (MDD) in multiple domains. As differentiation between TD and MDD can be difficult, infants with MDD often miss opportunities for intervention. For many clinicians, the ongoing challenge is early detection of MDD without over servicing the population. This study aims to: (1) identify early clinical biomarkers for use in this population to predict and differentiate between TD and MDD at 24 months corrected age. (2) Determine the extent to which family and caregiver factors will contribute to neurodevelopmental and behavioural outcomes. Methods and analysis: Participants will be a prospective cohort of 90 infants (<32 weeks and/or <1500 g). Between 34 weeks gestational age and 16 weeks post-term, infants will have a series of 5 neurological, neuromotor, neurobehavioural and perceptual assessments including General Movement Assessment at preterm, writhing and fidgety age. Primary caregivers will complete questionnaires to identify social risk, maternal depression and family strain. Extensive perinatal data will be collected from the medical record. At 24 months, corrected age (c.a) infants will be assessed using standardised tools including the Bayley Scales of Infant and Toddler Development—Third Edition (Bayley III). Longitudinal trajectories of early assessment findings will be examined to determine any predictive relationship with motor and cognitive outcomes at 24 months c.a. Published data of a cohort of Australian children assessed with the Bayley III at 24 months c.a will provide a reference group of term-born controls. Ethics: Ethical approval has been obtained from the Queensland Children's Health Services Human Research Ethics Committee (HREC/13/QRCH/66), the University of Queensland (2013001019) and the Sunshine Coast Hospital and Health Service, SC-Research Governance (SSA/13/QNB/66). Publication of all study outcomes will be in peer-reviewed journals. Trial registration number: ACTRN12614000480684; Pre-results.